2016
DOI: 10.1091/mbc.e16-04-0209
|View full text |Cite
|
Sign up to set email alerts
|

TSSC1 is novel component of the endosomal retrieval machinery

Abstract: A previously uncharacterized WD40 domain–containing protein named TSSC1 is shown to interact with the GARP and EARP tethering complexes, promoting retrograde transport of Shiga toxin from endosomes to the TGN, as well as recycling internalized transferrin from endosomes to the plasma membrane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
31
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 60 publications
6
31
0
Order By: Relevance
“…The results presented here show that kish/TMEM167A, a protein previously associated with vesicle transport and secretion (Gershlick et al, 2016;Wendler et al, 2010), is necessary for glioma growth, both in human cell xenografts and Drosophila models. Mechanistically, kish/TMEM167A downregulation alters the endo-lysosomal system.…”
Section: Discussionmentioning
confidence: 58%
“…The results presented here show that kish/TMEM167A, a protein previously associated with vesicle transport and secretion (Gershlick et al, 2016;Wendler et al, 2010), is necessary for glioma growth, both in human cell xenografts and Drosophila models. Mechanistically, kish/TMEM167A downregulation alters the endo-lysosomal system.…”
Section: Discussionmentioning
confidence: 58%
“…EARP is required for the recycling of cargos from recycling endosomes back to the plasma membrane (Schindler, Chen, et al, 2015). EIPR1 was also shown to be required for the endocytic recycling of transferrin in HAP1 cells (Gershlick et al, 2016).…”
Section: Eipr1 Is Required For Earp Function But Not Garp Functionmentioning
confidence: 98%
“…It was recently shown that mammalian EIPR1 interacts with the EARP and GARP complex subunits and functions with EARP in endosomal recycling and with GARP in endosome-Golgi retrograde trafficking (Gershlick et al, 2016;Topalidou et al, 2016).…”
Section: Eipr1 Is Needed For the Localization Of Earp Subunits And Thmentioning
confidence: 99%
See 2 more Smart Citations